Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Rumah Makan Wong Solo Cabang Lampriet Banda Aceh - Rudi Ramadhan; Yulindawati Y; Marwiyati M (Jurnal Ilmiah Mahasiswa Ekonomi dan Bisnis Islam, 2021)
The results of the study found that there was a simultaneous influence on aspects of service reliability, responsiveness, assurance, empathy, and physical evidence on customer satisfaction. Partially, only the responsiveness aspect has an insignificant effect, the other four aspects have a significant influence. The influence of service quality aspects on customer satisfaction is 42.6% and the rest is 57.4%, influenced by other factors outside the variables of this study. Seeing the aspect of responsiveness that is not significant, it is recommended that management improve performance on the aspect of responsiveness to be more alert and fast in providing services to customers.